2012
DOI: 10.1021/jf302070y
|View full text |Cite
|
Sign up to set email alerts
|

Double Spike Isotope Dilution GC-ICP-MS for Evaluation of Mercury Species Transformation in Real Fish Samples Using Ultrasound-Assisted Extraction

Abstract: Sample preparation continues being a key factor to obtain fast and reliable quantification of Hg species. Assisted procedures enhance the efficiency and reduce the extraction time; however, collateral species transformations have been observed. Moreover, differential interconversions have been observed even between similar matrixes, which introduce an important uncertainty for real sample analysis. Trying to minimize Hg species transformations, we have tested a soft ultrasound-assisted extraction procedure. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Three different extraction methods were used: (a) heating at 85 C for two hours, (b) MAE at 60 W for three minutes and (c) standing at room temperature for 24 hours, with TMAH employed as the extractant in each case. The spike isotopes used were 199 Hg for inorganic Hg and 201 Hg for MeHg. Mercury species were simultaneously derivatised and extracted in situ, with 1% sodium tetrapropyl borate (NaPr 4 B) in a sodium acetate/acetic acid buffer at pH 4 into isooctane, prior to GC separation and isotope ratio measurements by ICP-MS. A MXT-1 column (length 30 m, i.d.…”
Section: Mercurymentioning
confidence: 99%
See 3 more Smart Citations
“…Three different extraction methods were used: (a) heating at 85 C for two hours, (b) MAE at 60 W for three minutes and (c) standing at room temperature for 24 hours, with TMAH employed as the extractant in each case. The spike isotopes used were 199 Hg for inorganic Hg and 201 Hg for MeHg. Mercury species were simultaneously derivatised and extracted in situ, with 1% sodium tetrapropyl borate (NaPr 4 B) in a sodium acetate/acetic acid buffer at pH 4 into isooctane, prior to GC separation and isotope ratio measurements by ICP-MS. A MXT-1 column (length 30 m, i.d.…”
Section: Mercurymentioning
confidence: 99%
“…It was reported that signicant mercury species transformation was only observed for one oyster sample resulting in 18% demethylation of inorganic Hg. In a separate paper, 201 double spiking IDA was also described in the investigation of UAE of Hg species in sh samples. Four different extraction solutions, (5 mol L À1 HCl, 60 mmol L À1 HCL in saturated NaCl, 3.0 mol L À1 KOH in MeOH and 25% TMAH in H 2 O), were evaluated in this work.…”
Section: Mercurymentioning
confidence: 99%
See 2 more Smart Citations
“…(2) The development of a robust method for the accurate and sensitive determination of each mercury species in various seafood samples is necessary. In reality, the most practical analytical methods for mercury speciation are inductively coupled plasma mass spectrometry (ICP-MS)-based hyphenated techniques such as high performance liquid chromatography (HPLC) hyphenated with ICP-MS (HPLC-ICP-MS), 10,11,[14][15][16][17][18][19][20][21][22] ion chromatography hyphenated with inductively coupled plasma mass spectrometry (IC-ICP-MS), 8,9,23 gas chromatography (GC) hyphenated with ICP-MS (GC-ICP-MS) and capillary electrophoresis (CE) hyphenated with ICP-MS (CE-ICP-MS), 6,[24][25][26] although several sensing methods including colorimetric and uorescence methods have been developed for the rapid and specic determination of CH 3 Hg + and/or C 2 H 5 Hg + in recent years. [27][28][29] Among all ICP-MS-based techniques, CE-ICP-MS has lower sensitivity and poorer repeatability due to the low sample injection volume, 6,26 whereas most HPLC-ICP-MS methods previously reported employed an expensive reverse-phase C18 or C8 column as the separation column and thus involved higher analysis cost.…”
Section: Introductionmentioning
confidence: 99%